A Morphological Analysis: A Trend of the English Suffix “-less” in Indonesian Words on X/Twitter - Septiana, Ade Ayu; Kirana, Anisa Febriani Puspa; Mahadewi, Riska Iswanda Utami; Sujatna, Eva Tuckyta Sari (Indonesian Journal Publisher, 2024)
The widespread use of English by people from various parts of the world has led to the emergence of new vocabulary, including the process of affixation between English and Indonesian words. By analyzing samples of common Indonesian words attached with the suffix ‘-less’, this research aims to discuss the use of the suffix ‘-less’ in Indonesian words and how it is used in context. The method used in this research is descriptive qualitative. Data sources were obtained from Indonesian words containing the suffix ‘-less’ that appear in posts, comments, and quotes from X/Twitter users in Indonesia. The data then analyzed based on the theory of word formation as a sub discipline of morphology by Lieber (2009). This research finds that the application of the suffix ‘-less’ is more often found attached to nouns and is rarely found attached to verbs.